Case report: Ultrahypofractionated palliative breast radiotherapy for a fungating invasive mammary carcinoma - Hong, Yejun; Nixon, Nancy; Cao, Jeffrey Q.; Lee, Sangjune Laurence (Frontiers in Oncology, 2023)
Palliative radiotherapy for symptomatic and intact breast tumors must balance convenience, efficacy, and risk of acute toxicity. This case report presents a patient with metastatic breast cancer and an intact fungating primary tumor. She was treated with an ultrahypofractionated radiation therapy, 26 Gy in 5 consecutive daily fractions, with sequential palliative chemotherapy. This resulted in a minimal toxicity profile and significant reduction of tumor burden and symptoms.